Regional-Scale Seismic Liquefaction Susceptibility Mapping via an Empirical Approach Validated by Site-Specific Analyses - Veronica Zumpano; Luca Pisano; Francesco Filice; Angelo Ugenti; Daniela de Lucia; Janusz Wasowski; Francesca Santaloia; Piernicola Lollino (Geosciences, 2022)
Regional-scale analyses of susceptibility to liquefaction are seldom performed in data-scarce areas. However, in spite of data limitations, such efforts can still provide useful information in case of populated, seismically active regions. The present work focuses on susceptibility zonation for soil liquefaction that might occur due to ground shaking in the Foggia Province, a data-scarce, seismically active area of about 7000 km2 located in southern Italy. The Analytical Hierarchy Process (AHP) approach is used to obtain the susceptibility to liquefaction map of the whole area, while a geological and geotechnical database including 531 boreholes from 84 localities is used for cross-validation. The data are processed by means of a simplified quantitative method to determine liquefaction potential and assess whether a specific area is prone to liquefaction or not. Our results, along with an AUC − ROC = 0.89 test value, indicate that there are widespread areas of medium to high and very high susceptibility, and that the most susceptible zones are localized along the Adriatic Sea coastline and watercourses. The final susceptibility to liquefaction map represents a step forward towards the assessment of secondary seismic hazard in the study area, thus supporting the regional and local administrations responsible for land-use planning and risk mitigation.